Proteomics discovery of novel biomarkers for diagnosis and stratification of patient at risk for atherosclerotic cardiovascular diseases - Cheow, Esther Sok Hwee (2017)
Atherosclerotic coronary artery disease (CAD)-related deaths will continue to rise along with global population ageing. Although established conventional risk factors are in place for the prediction of cardiovascular (CV) events, however, the absence does not necessarily imply zero CAD risk. Effective screening and diagnostic methods that stratify patient at high risk for CAD, before onset of acute events, remain unsatisfactory, necessitating the search for novel measurable protein biomarkers. Thankfully, biomarker discovery has taken a leap forward with the development of mass spectrometry (MS)-based proteomics approaches, which afforded the interrogation of the plasma proteome. The incomplete understanding in the mechanisms in plaque destabilization and rupture, creates a knowledge gap in the pathophysiological underlying atherosclerosis and myocardial infraction (MI). In addition, currently there is no plasma-based screening assay that effectively differentiates atherosclerosis from MI. The development of innovative techniques that improves the detectable range of plasma pro teo me, is essential in advancing the field of plasma-based biomarker discovery research. My PhD research work has been divided into four parts (I - IV), the first three parts showcased the clinical utility of the plasma proteome for CAD proteomics-based biomarker discovery, and in the final part, and the successful development of a novel enrichment strategy for plasma glycoproteins and extracellular vesicles (EV) was demonstrated. Herein, the careful selection and systematic integration of several proteomics strategies have proven useful in the discovery of novel plasma biomarkers of CAD, derived from (i) undepleted plasma proteome, (ii) EV plasma proteome and (iii) carbamylated plasma proteome. Functional linkage analyses have prompted the generation of new hypotheses into the pathophysiological states that specifies either for atherosclerosis or myocardial injury. The novel plasma sub-proteome enrichment technique described here have afforded the detection of low-abundant proteins with concentration ranging from pg/mL- ng/mL in crude plasma. In essence, this thesis demonstrates the applicability and reliability of the different proteomics platforms in the discovery and development of useful biomarkers that are predictive of CAD.